Development of a Valid and Reliable Knee Articular Cartilage Condition–Specific Study Methodological Quality Score. Issue 2 (7th February 2014) - Harris, Joshua D.; Erickson, Brandon J.; Cvetanovich, Gregory L.; Abrams, Geoffrey D.; McCormick, Frank M.; Gupta, Anil K.; Verma, Nikhil N.; Bach, Bernard R.; Cole, Brian J.
Background: Condition-specific questionnaires are important components in evaluation of outcomes of surgical interventions. No condition-specific study methodological quality questionnaire exists for evaluation of outcomes of articular cartilage surgery in the knee. Purpose: To develop a reliable and valid knee articular cartilage–specific study methodological quality questionnaire. Study Design: Cross-sectional study. Methods: A stepwise, a priori–designed framework was created for development of a novel questionnaire. Relevant items to the topic were identified and extracted from a recent systematic review of 194 investigations of knee articular cartilage surgery. In addition, relevant items from existing generic study methodological quality questionnaires were identified. Items for a preliminary questionnaire were generated. Redundant and irrelevant items were eliminated, and acceptable items modified. The instrument was pretested and items weighed. The instrument, the MARK score (Methodological quality of ARticular cartilage studies of the Knee), was tested for validity (criterion validity) and reliability (inter- and intraobserver). Results: A 19-item, 3-domain MARK score was developed. The 100-point scale score demonstrated face validity (focus group of 8 orthopaedic surgeons) and criterion validity (strong correlation to Cochrane Quality Assessment score and Modified Coleman Methodology Score). Interobserver reliability for the overall score was good (intraclass correlation coefficient [ICC], 0.842), and for all individual items of the MARK score, acceptable to perfect (ICC, 0.70-1.000). Intraobserver reliability ICC assessed over a 3-week interval was strong for 2 reviewers (≥0.90). Conclusion: The MARK score is a valid and reliable knee articular cartilage condition–specific study methodological quality instrument. Clinical Relevance: This condition-specific questionnaire may be used to evaluate the quality of studies reporting outcomes of articular cartilage surgery in the knee.